Utility of transient elastography in evaluation and follow-up of Budd-Chiari syndrome patients after endovascular intervention - Hend Elsaied Ebada; Mohamed Fawzy Montasser; Eman Fathy Barakat; Sara Mahmoud Abdelhakam; Mohamed Shaker Ghazy; Ahmed Talaat Elganzory (SpringerOpen, 2021)
Abstract Background Liver stiffness measurement (LSM) using transient elastography (TE) is a common noninvasive method for assessing hepatic fibrosis. The purpose of this study was to show the utility of LSM in the evaluation and short-term follow-up of Budd-Chiarri syndrome (BCS) patients as well as to investigate the relationships between LSM, hepatic venous pressure, and liver fibrosis. We conducted a prospective cohort study in which 25 patients with a confirmed diagnosis of primary BCS underwent endovascular intervention for BCS treatment. All patients had pressure gradient changes across the stenosed hepatic veins/inferior vena cava (HV/IVC) measured before and after the procedure, a transvenous liver biopsy during the procedure, and LSM (using Transient Elastography 3 days before and 3 months after the intervention as a short-term follow-up). Comparisons and correlations were made between liver stiffness, hepatic venous pressure, and fibrosis. Results The HV/IVC pressure gradient measured immediately before and after the intervention had a direct proportionate correlation with the LS measured 3 days before and 3 months after the intervention (r = 0.41 & 0.44, p: 0.04 & 0.03, respectively). LSM drops significantly 3 months after intervention (from 51.62 ± 22 kPa to 28.80 ± 19.25 kPa (p: 0.001)). There is a significant improvement in LSM post-intervention among patients with moderate to severe fibrosis (METAVIR scores of ≥ F2 before intervention (p: 0.001). Conclusions LSM in BCS patients reflects congestion rather than fibrosis stage. TE can be used for the short-term monitoring of patients with BCS following the endovascular intervention as a noninvasive tool.